Local Government: Challenges Faced in the implementation of 73rd constitutional amendment act 1992 (International Journal of Food and Nutritional Sciences, 2022)
By introducing 73rd Constitutional amendment act 1992, Government of India made an attempt to decentralize Panchayati Raj Institutions. Thirty years of decentralization of local government has been completed by India after its implementation in 1992. This was the foundation of real democracy. Local Government is a platform through which common man can take part in decision making process of the country. There was an inclusion of deprived sections of the society to the mainstream. Decentralization of local government has a direct link with rural development. A rural society has local culture and local needs. It is only at the gram panchayat level that local problems or needs of the people can be identified. As a result of 73rd constitutional amendment act, the reservation policies for SC, ST and women have been introduced. This research paper has made an attempt to analyze the challenges faced in the implementation of 73rd constitutional amendment act 1992. Many important provisions were introduced and a uniform structure at Gram panchayat, Panchayat Samiti and Zila Parishad level came it to existence. Findings of the study shows that local government is not functioning well and there are lot of problems faced by general public.